Intersectionality and Legal Recognition of Women's Role in Health-Related Family Decision-Making: Revisiting Reproductive and Neonatal Rights - Dr. Sanjeev Kumar, Prof. (Dr.) Sanjeet Singh (Journal of Neonatal Surgery, 2025)
In this paper, we analyze how legal recognition of women's agency in health-related family decision-making, including reproductive and neonatal rights overlaps with the differential impact of various markers of identity such as, but not limited to, gender, race, and socioeconomic status. By employing a critical feminist jurisprudential framework, the paper examines the historical and current landscapes of law and policy that shape and limit the decision-making power of women. This analysis provides insight into the ongoing inequities in the law as they affect women with intersecting identities, and exposes the degree to which women belonging to multiple marginalized groups face compounded obstacles in asserting their right to decide how to care for their families. Legal paradigms frequently bypass the range of social determinants that inform women's health behavior by falling back on paternalistic or family-centered approaches that reduce autonomy. This paper advocates for reframing of health decision-making rights from an intersectional perspective in the context of the family, where respect for women's body autonomy is preserved. The paper ends with proposed reforms to the law itself that take an intersectional approach to provide fair treatment to women across populations in how their decision-making power is considered.